Drawing it together - Bain, Murray; James, Colin (New Zealand Science Review, 2011)
​Colin James and I drew lots as to who would speak first and as usual, the fourth estate gets the last word. But this is great timing for me as the recently appointed chief executive of the new Ministry of Science and Innovation. I congratulate the organisers who have so presciently figured out this would be a very good time to get some stuff on the table about science and innovation. Today has been a very useful one for me but there’s always the challenge, isn’t there, of drawing it together. Colin will do that much more succinctly than I. However, I’ve got a few thoughts that I’m interested in sharing with you.